Characteristics of Epileptiform Discharge Duration and Interdischarge Interval in Genetic Generalized Epilepsies - Seneviratne, Udaya; Boston, Ray C.; Cook, Mark J.; D’Souza, Wendyl J. (Frontiers in Neurology, 2018)
We sought to investigate (1) the characteristics of epileptiform discharge (ED) duration and inter-discharge interval (IDI) and (2) the influence of vigilance state on the ED duration and IDI in genetic generalized epilepsy (GGE). In a cohort of patients diagnosed with GGE, 24-hour ambulatory EEG recordings were performed prospectively. We then tabulated durations, IDI, and vigilance state in relation to all EDs captured on EEGs. We used K-means cluster analysis and finite mixture modeling to quantify and characterize the groups of ED duration and IDI. To investigate the influence of sleep, we calculated the mean, median, and standard error of the mean in each population from all subjects for sleep state and wakefulness separately, followed by the Kruskal-Wallis test to compare the groups. We analyzed 4679 epileptiform discharges and corresponding IDI from 23 abnormal 24-hour ambulatory EEGs. Our analysis defined two populations of ED durations and IDI; short and long. In all populations, both ED durations and IDI were significantly longer in wakefulness. Our results highlight different characteristics of epileptiform discharge populations in GGE and the influence by the sleep-wake cycle.